2018
DOI: 10.1016/j.cimid.2018.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Changes in salivary analytes in canine parvovirus: A high-resolution quantitative proteomic study

Abstract: A B S T R A C TThe present study evaluated the changes in salivary proteome in parvoviral enteritis (PVE) in dogs through a high-throughput quantitative proteomic analysis. Saliva samples from healthy dogs and dogs with severe parvovirosis that survived or perished due to the disease were analysed and compared by Tandem Mass Tags (TMT) analysis. Proteomic analysis quantified 1516 peptides, and 287 (corresponding to 190 proteins) showed significantly different abundances between studied groups. Ten proteins wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 78 publications
1
11
0
Order By: Relevance
“…Among them, C8A and several uncharacterized proteins (compatible with immunoglobulins according to their BLAST sequence) were the most up‐regulated. This increase of C8A level could be related to the activation of complement cascade, similarly to that described in the case of other inflammatory diseases such as canine babesiosis (Kuleš et al, ) or parvovirosis (Franco‐Martínez et al, ). Thus, the increase in C8A could point out the activation of complement cascade in response to the diffusion of Leishmania through the organism.…”
Section: Discussionsupporting
confidence: 67%
“…Among them, C8A and several uncharacterized proteins (compatible with immunoglobulins according to their BLAST sequence) were the most up‐regulated. This increase of C8A level could be related to the activation of complement cascade, similarly to that described in the case of other inflammatory diseases such as canine babesiosis (Kuleš et al, ) or parvovirosis (Franco‐Martínez et al, ). Thus, the increase in C8A could point out the activation of complement cascade in response to the diffusion of Leishmania through the organism.…”
Section: Discussionsupporting
confidence: 67%
“…A total of 35 µg of protein per sample was subjected to reduction, alkylation, digestion and labelling using 6-plex Tandem Mass Tag reagents, according to manufacturer instructions (Thermo Scientific) as described previously [10,11]. In brief, after protein determination using Bradford assay [21], 35 µg of sample and internal standards (consisting of a pool of 35 µg of each sample) were reduced for 1 h with 200 mM DTT (Sigma-Aldrich), alkylated for 30 min with 375 mM iodoacetamide (Sigma-Aldrich) and precipitated with ice-cold acetone (VWR, Llinars del Vallés, Barcelona, Spain).…”
Section: Proteomics Study Of Saliva and Serum Samples And Lc-ms/ms Anmentioning
confidence: 99%
“…In humans, proteomic analyses of saliva have proved to be a useful technique for discovering disease-related biomarkers in different pathologies including cancer [8]. In dogs, gel-free proteomics approaches such as Tandem Mass Tag (TMT) have been successfully used in serum and/or saliva in different infectious diseases such as pyometra [9], parvoviral enteritis [10] and leishmaniosis [11], as well as for metabolic diseases such as obesity [12].…”
Section: Introductionmentioning
confidence: 99%
“…A P < 0.05 value was considered to be significant. Fold changes (FC) have been obtained with the formula FC=log2 (Group before /Group after) as has been reported before (Franco-Martínez et al, 2018). RStudio (v1.0.143) (R Studio Team.…”
Section: Discussionmentioning
confidence: 99%
“…These novel technologies that employ isobaric tags have emerged in the last few years and are becoming widely employed, since they are highly reproducible and sensitive and allow for the relative simultaneous quantification of differentially labelled peptides (Baeumlisberger et al, 2010;Dayon et al, 2011;Giron et al, 2011). In veterinary science, recent investigations using these novel quantitative technologies to detect possible biomarkers of diagnostic and understand the prognosis of diseases in dogs (Martínez-Subiela et al, 2017;Franco-Martínez et al, 2018) have been reported. Also, studies performed in sheep using these techniques to evaluate the alterations in the intestine associated with under weaning stress using jejunum samples (Cui et al, 2018) or to consider age-related changes in the cerebrospinal fluid (Chen et al, 2018) have been published.…”
Section: Introductionmentioning
confidence: 99%